TRIASSIC STRATIGRAPHY IN THE ISLAND OF HYDRA (GREECE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
The Triassic sedimentary succession, cropping our in the island of Hydra, starts with a few metres of quartzarenites (Aghios Nikolaos Fm., Scythian) vertically making transition to a thick carbonate unit (Eros Lmst., Spathian-Pelsonian) subdivided into three lithozones and one member. During Pelsonian an extensional tectonic phase dissects the Eros carbonate platform. Its consequent downwarping results in the deposition of a pelagic sequence spanning the Pelsonian-Late Triassic time interval. This succession generally consists of few metres of nodular limestones (Han Bulog Lmst., Late Pelsonian-Early Ladinian) associated with green tuffs, followed by few hundred metres of cherty limestones (Adhami Lmst.). In the eastern part of the island a thick carbonate bank (Pantokrator Lmst.) develops, spanning the lllyrian to Late Triassic time interval. An overlying pelagic sequence, Jurassic in age, marks the downwarping of the Pantokrator carbonate platform. A typical passive continental margin succession is thus recorded in the Triassic of Hydra, suggesting its affinity with the Subpelagonian domain.
Keywords: Biostratigraphy; Foraminifers; Conodonts; Triassic; Hellenides.